INTERNAL FACTORS INFLUENCING THE IMPLEMENTATION OF SAK EMKM AMONG MSMES IN SURAKARTA CITY - Erlinta Sheila Mahendra; Putri Intan Prastiwi; Novemy Triyandari Nugroho (CV. Adiba Aisha Amira, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth; however, the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among the majority of MSMEs remains suboptimal. This situation suggests the presence of internal factors influencing the application of accounting standards in financial statement preparation. Small and medium-sized businesses in Surakarta City use SAK EMKM, and this usage is affected by factors like their sales volume, how long they've been operating, and their business size. This study employed a quantitative research approach. The sample included 100 MSME owners who were chosen using purposive sampling. Data was gathered using questionnaires and then looked at using multiple linear regression analysis. The findings show that the age of the business and the owner's education level have a positive and important influence on implementing SAK EMKM.However, the business's sales volume and size do not play a major role. All the different factors together have a big impact on how well SAK EMKM is done. The Adjusted R-Square value is 0.600, which means the model explains 60% of the differences in how SAK EMKM is carried out. The findings suggest that the business owner's experience and education level are more decisive factors than business characteristics—such as turnover and size—in fostering the adoption of SAK EMKM. Therefore, continued efforts in education, training, and accounting assistance for MSME owners are essential to support more optimal SAK EMKM implementation.